(3QSGdI aj Yde GdJLhjO hbhGYOg hCMcGeg hMQhags - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj fYeJg MeO CeG HYO agPg QSGdI eTJedI Ydi Yde GdJLhjO hbhGYOg hCMcGeg hMQhag hOdGdJg GdCQHYI agj GdEOZGe hGdEXgGQ hGdCbd hGdENaGAs
(3BNQgG (B:s
(3dCf jMLR eG Hjf GdSGcfjf hCUdg dGRe eKbd cdej hbS Ydi Pdc aGage CjgG GdWGdH gPg GdMGdGJs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs